Mechanism of Bushen Zhuangjin Decoction to Promote BMSCs Homing and Protect Articular Cartilage in Mice by the SDF-1/CXCR4 Axis - HUANG Yanfeng; MA Dezun; FU Changlong; YE Jinxia; HUANG Yunmei; LI Xihai (康复学报)
ObjectiveTo investigate the mechanism by which Bushen Zhuangjin Decoction (BZD) regulates the SDF-1/CXCR4 axis to promote the homing of bone marrow mesenchymal stem cells (BMSCs) and protect articular cartilage in mice, thereby providing experimental basis for the rehabilitation treatment of knee osteoarthritis (KOA).Methods(1) In the animal experiment, 30 SPF male C57BL/6 mice, 8 weeks old, were selected and randomly divided into sham group, model group and BZD group, with 10 mice in each group. Intervention in each group lasted for 12 weeks. The morphological changes of the cartilage in each group were observed by micro-CT and hematoxylin-eosin staining. The fluorescence intensity of SDF-1 in bone tissue was observed by laser confocal microscopy. qPCR and Western blot were used to detect mRNA transcription level and protein relative expression level of homing-related regulatory factors in each group. (2) In the cell experiment, 4-week-old SPF male C57BL/6 mice were selected and the primary BMSCs were extracted by the whole bone marrow adherence method. After the extracted cells were identified by flow cytometry, the optimal lentivirus MOI value was screened. The cells were randomly divided into five groups: blank group, empty vector group, BZD group, sh-SDF-1 group and sh-SDF-1+BZD group. The migration of BMSCs in each group was observed by cell scratch test. The chondrogenic differentiation ability of cells in each group was observed by immunocytological staining of Collagen Ⅱ and Alcian blue. The fluorescence intensity of SDF-1 and CXCR4 in each group was observed by confocal laser microscope. mRNA transcription level of homing-related regulatory factors were detected by qPCR.Results(1) In the animal experiment, the joint histomorphologic findings (micro-CT and hematoxylin-eosin staining) showed that compared with the sham group, there was a circular defect between the femoral condyles, with cortical separation and loss of chondrocytes in the model group (P<0.05); compared with the model group, the annular defect between the femoral condyles was improved and the arrangement of chondrocytes was slightly disordered in the BZD group. The immunofluorescence staining of joint tissues showed that compared with the sham group, the relative expression of SDF-1 protein increased in the model group (P<0.05); compared with the model group, the relative expression level of SDF-1 increased in the BZD group (P<0.05). qPCR and Western blot results showed that compared with the sham group, the mRNA transcription level and protein relative expression level of key homing regulatory factors (SDF-1, CXCR4, MIP-1α, MCP-1, MIP-1β, RANTES, VEGF, G-CSF, NCAM-1, MMP-2) increased in the model group (P<0.05); compared with the model group, the mRNA transcription level and relative protein expression level of key homing regulatory factors increased in the BZD group (P<0.05). (2) In the cell experiment, BMSCs were identified by flow cytometry: CD44 and CD105 were positively expressed, while CD34 was negatively expressed. When the MOI value was 100, the infection rate of SDF-1 gene was the highest. The results of BMSCs migration and chondrogenic differentiation showed that the number of cells migrating to the scratched area, the relative expression of Collagen Ⅱ protein, and acid mucosaccharide of sh-SDF-1 cells were significantly reduced compared with the blank group. The number of migrated cells, Alcian blue staining and the relative expression of Collagen Ⅱ protein significantly increased in the BZD group and the sh-SDF-1+BZD group (P<0.05). Immunofluorescence finding showed that compared with the blank group, the relative protein expression of SDF-1 and CXCR4 in the sh-SDF-1 group was significantly reduced (P<0.05), while the relative protein expression of SDF-1 and CXCR4 significantly increased in the BZD group and the sh-SDF-1+BZD group (P<0.05). qPCR results showed that compared with the blank group, the mRNA transcription level of key homing regulatory factors decreased in the sh-SDF-1 group (P<0.05), while those increased in the BZD group (P<0.05).ConclusionBZD can promote the homing of BMSCs to protect articular cartilage in mice by upregulating the SDF-1/CXCR4 axis.